IDENTIFIKASI PARASETAMOL DALAM JAMU PEGAL LINU YANG DIPEROLEH DARI DEPOT JAMU DI KOTA DENPASAR - Ni Made, Maharia Ningsih (Jurnal Riset Kefarmasian Indonesia, 2022)
The use of traditional medicine in the form of herbal medicine is in great demand by the people of Indonesia, one of that is pegal linu herb. Based on PERMENKES No. 006/Menkes/Per/V/2012 articles 33 and 37 states that traditional medicine may not contain medicinal chemical. Medicinal chemical that is often added into herbal medicine for pegal linu herb is paracetamol.This study aims to determine the presence of paracetamol in pegal linu herb depots in Denpasar city. The research method used an exploratory descriptive method and samples of herbal medicine were taken by purposive sampling, 14 samples of herbal medicine of various brands that was sold at depots in Denpasar City. The research was conducted at the chemical laboratory of Bali International University in July 2021. After preparation, the fourteen samples of herbal medicine were identified using Thin Layer Chromatography (TLC) with selection mobile phase ethanol p.a, detection with UV light 254 nm and 0.05 M H2SO4 sprayer. Completeness identification was also carried out descriptive labeling of herbal products containing paracetamol. Positive samples contain paracetamol if the Rf value and spot color are similar to the paracetamol comparison standard. The Rf results obtained that samples with codes F, I, K, and L were 0.68; 0.68; 0.68 and 0.68 which are the similar as the standard Rf for comparison of paracetamol and positive control which is 0.69. The conclusion of the research is that there are various brands of pegal linu herb sold in Indonesia that are suspected to contain 4 brands of paracetamol. Research suggestions for consumers who consume a brand of traditional herbal medicine are expected to be more selective in choosing herbal medicine by first checking the product registration number.